Effect of Cassia roxburghii as a phytogenic feed additive on growth performance, nutrient utilisation and health of Oreochromis mossambicus - Nithin Jacob (KUFOS, 2018)
Abstract- Phytogenics are a group of natural growth promoters (NGPs) or non-antibiotic growth promoters used as feed additives, derived from herbs, spices or other plants. Phytogenic feed additives are an extremely heterogeneous group of feed additives originating from leaves, roots, tubers or fruits of herbs, spices or other plants. The unnecessary and excessive use of antibiotics in aquaculture cause spread of antibiotic resistance in zoonotic bacterial pathogens, which poses a threat to environmentalas well as to public health.The use of phytobiotics with pharmacological effects has gained attention in aquaculture since the variety and availability of plants with potential bioactive properties is very high. Additionally, the use of plant products as immunostimulants in aquaculture systems may also be of environmental value due to their biodegradability. The aim of current investigation was to evaluate the effectsof Cassia roxburghii as a phytogenic feed additive on growth performance, nutrient utilisation and health of Oreochromismossambicus(Tilapia).A total of 240 apparently healthy Oreochromis mossambicuswith an average body weight of 15.50 ± 0.12g were used. The fish were randomly divided into 12 equal triplicate groups (each replicate contained 20 fish). The fish were fed iso-nitrogenous (30%CP), iso-lipidic (6%) diets with different extracts (1%) of Cassia roxburghii leaf, seed, and bark extract thrice daily, at 10:00 and 13.00 and 17:00 h for 60 days ad libitum. The water quality parameters like pH, DO, temperature, and ammonia nitrogen as well as growth response were monitored weekly basis. The water quality maintained by 50% replacement of water every week. On termination of trial, the fish fed with Cassia roxburghiibark extract showed significant (P < 0.05) increase in total final body weight(109.93 ± 1.11g ), weight gain(94.25 ± 1.07g), weight gain percentage(598.71 ± 5.46), specific growth rate(3.24 ± 0.01). The nutrient utilisation factors like FER (0.84 ± 0.03), PER (2.86 ± 0.09), PRE (58.84 ± 1.72) also exhibited significant increase (P<0.05) as compared to other extract fed groups and control. The utilisation efficiency was also found to be superior in treatment 3 (bark extract) evidenced by the lower food conversion ratio (1.16±0.03). The proximate composition of fish sample revealed that, better crude protein and crude lipid percentage obtained in bark extract fed group. The same group showed low moisture and ash content from other treatments. The blood biochemical constituents like total serum protein, albumin, triglyceride, HDL, VLDL, SGOT, SGPT, alkaline phosphatase were high in control group. The bark extract fed group exhibited higher cholesterol level and lower level of SGOT, SGPT and alkaline phosphatase. Lower values of haemoglobin, serum total protein, glucose, triglyceride, HDL, VLDL, were observed in seed extract fed group. The leaf extract did not show any significant effect on fish in comparison to other treatments. The histological changes found in the intestine include, increase in length, height, number of folds of villi and large number of scattered goblet cells. It could be concluded that supplementationof Cassia roxburghii bark extract in fish diets improve its growth, nutrient utilisation, and health in Orechromis mossambicus (Tilapia).